Motile Cilia: Innovation and Insight From Ciliate Model Organisms - Bayless, Brian A.; Navarro, Francesca M.; Winey, Mark (Frontiers in Cell and Developmental Biology, 2019)
Ciliates are a powerful model organism for the study of basal bodies and motile cilia. These single-celled protists contain hundreds of cilia organized in an array making them an ideal system for both light and electron microscopy studies. Isolation and subsequent proteomic analysis of both cilia and basal bodies have been carried out to great success in ciliates. These studies reveal that ciliates share remarkable protein conservation with metazoans and have identified a number of essential basal body/ciliary proteins. Ciliates also boast a genetic and molecular toolbox that allows for facile manipulation of ciliary genes. Reverse genetics studies in ciliates have expanded our understanding of how cilia are positioned within an array, assembled, stabilized, and function at a molecular level. The advantages of cilia number coupled with a robust genetic and molecular toolbox have established ciliates as an ideal system for motile cilia and basal body research and prove a promising system for future research.